PERANAN MEDIATOR DALAM PENYELESAIAN PERKARA CERAI GUGAT DI PENGADILAN AGAMA PEKANBARU - Nurvita, Nita; Hanifah, Mardalena; Hendra, Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
All cases that are not included in the exclusion criteria has to mediation first, not exception divorse case in religious courts.on these conditions, expected that the parties can find and see the positive side of the mediation proses offered with the assistance of a neutral mediator.Mediator is neutral meaning that doesn’t take sides (impartial), doesn’t have interest in disputes and does’t gain and lose if the dispute can be resolved or not completed or if mediation meet (deadlock). Mediator has a decisive of mediator.mediation is also determine by the mediator. The purpose of this research is to determine the effectiveness, role of mediator for resolvingdivorce cases in Pekanbaru religious court and things that become obstacles for mediator in resolving divorce cases in Pekanbaru religious court.Key Words: Mediation – Mediator – Role